2021
DOI: 10.3389/fimmu.2021.722170
|View full text |Cite
|
Sign up to set email alerts
|

Periostin in Allergy and Inflammation

Abstract: Matricellular proteins are involved in the crosstalk between cells and their environment and thus play an important role in allergic and inflammatory reactions. Periostin, a matricellular protein, has several documented and multi-faceted roles in health and disease. It is differentially expressed, usually upregulated, in allergic conditions, a variety of inflammatory diseases as well as in cancer and contributes to the development and progression of these diseases. Periostin has also been shown to influence ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 142 publications
1
34
0
Order By: Relevance
“…[15][16][17] In particular, periostin was provided to be expressed in allergy, inflammation, fibrosis, and tumors for its promotive role in intermolecular interactions. 18,19 It has been reported that some of its activities were mediated by its binding to cell surface receptors of the integrin family. 19,20 The enhanced secretory function of heart proximal infarction area ensures the timeliness of fibrous repair and effectively prevents the occurrence of cardiac rupture.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In particular, periostin was provided to be expressed in allergy, inflammation, fibrosis, and tumors for its promotive role in intermolecular interactions. 18,19 It has been reported that some of its activities were mediated by its binding to cell surface receptors of the integrin family. 19,20 The enhanced secretory function of heart proximal infarction area ensures the timeliness of fibrous repair and effectively prevents the occurrence of cardiac rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin has potential to become a novel prognostic biomarker and treatment target for many diseases including chronic fibrosis, inflammation, allergy and cancer. Enhanced periostin levels can be detected in either tissue biopsy samples or serum, as periostin is secreted from pathologic tissue and transported into blood vessels ( 50 52 ). Several preclinical and clinical trials have been applied to demonstrate the efficacy of blocking periostin.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin, an extracellular matrix protein, is involved in the fibrosis of diseased tissues and plays a role in the pathogenesis of various diseases. 2 It has been reported that periostin regulates macrophage, vascular endothelial cell and smooth muscle cell functions. 3,4 Although several groups have demonstrated the contribution of periostin to the progression of pulmonary hypertension (PH), [4][5][6] its exact role is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Periostin, an extracellular matrix protein, is involved in the fibrosis of diseased tissues and plays a role in the pathogenesis of various diseases 2 . It has been reported that periostin regulates macrophage, vascular endothelial cell and smooth muscle cell functions 3,4 .…”
Section: Introductionmentioning
confidence: 99%